Influence of Eucalyptus camaldulensis Dehnh and Opuntia ficus-indica L. Mill in physical and chemical soil properties - Ortiz Torres, César; Gómez Díaz, Jesús David; Domínguez Álvarez, Francisco Alberto; Villanueva Morales, Antonio (REVISTA TERRA LATINOAMERICANA, 2018)
Forest plantations are a viable option for the afforestation of areas with degraded soils. Use of fast-growing species that adapt easily can accelerate the processes of recovering some physical, chemical and biological characteristics of the soil. The study was carried out in the plantation “Mario Ávila Hernández” established between 1960 and 1962 on land pertaining to Chapingo Autonomous University with the objective of rehabilitating eroded soils on the slopes of a hillside. To evaluate the impact of Eucaliptus camaldulensis Dehnh and Opuntia ficus-indica L. Mill, which were established for rehabilitation purposes, on the recovery of some soil properties, three one-hectare stands were selected.  Initially, the species E. camaldulensis Dehnh was established three meters apart on ruptured tepetates, and later, the species O. ficus-indica L. Mill appeared as an invasive species. The species was present in two stands and a third stand had only eucalyptus. The physical properties evaluated were bulk density (DAP), stability of aggregates (EA) and depth, while the chemical properties were total nitrogen (Nt), phosphorus (P), potassium (K), organic matter (MO) and pH. The plantation of E. camaldulensis has improved the condition of the ruptured tepetates, mainly through protection of the soil by the plant cover and the contribution of plant residues such as leaves, branches and detached bark, favoring an improvement in the physical and chemical soil properties evaluated. The results do not show differences in the physical and chemical properties of the soils when only E. camaldulensis is established or where this species is in association with O. ficus-indica. There were significant differences in potassium content only between the stand with one species and those with the two species; K was higher and pH lower in the stand with only Eucalyptus.